The Effectiveness of Psychoanalysis and Psychoanalytic Psychotherapy: A Literature Review of Recent International and Australian Research - Cadeyrn Gaskin (Psychotherapy and Counselling Journal of Australia)
The purpose of this review was to determine the effectiveness of psychoanalysis and psychoanalytic psychotherapy, both generally and in Australian settings. A systematic search for papers on research conducted internationally and in Australia within the last 5 years was undertaken using the Academic Search Complete, PsycINFO databases. From the 1,231 records retrieved from the two databases, 26 papers included studies that met the selection criteria. None of these papers contained research from Australia. Evidence from a small number of studies provides tentative support for the effectiveness of psychoanalysis in the treatment of patients with some depressive, anxiety, and personality disorders. The variable quality of this research, and the absence of control conditions in most studies, however, means that making more definitive statements about the effectiveness of psychoanalysis difficult at this time. The findings of studies on long-term psychoanalytic psychotherapy suggest that (a) favourable outcomes may be able to be achieved for people with a range of conditions, including mood, anxiety, sexual dysfunction, and personality disorders; (b) the outcomes achieved seem to be equivalent to those gained through the use of other psychotherapies; and (c) the effects of long-term psychoanalytic psychotherapy may endure long after the termination of treatment. Short-term psychoanalytic psychotherapy may be effective for the treatment of depressive disorders. The quality of studies in this area prevents the drawing of more definitive conclusions with respect to other conditions. Given that researchers often use the terms psychoanalytic and psychodynamic interchangeably, however, practitioners should be cognisant of the work on the effectiveness of psychodynamic psychotherapies. This work is supportive of the use of psychodynamic psychotherapy for depressive disorders, some anxiety disorders (most notably, generalised anxiety disorder), somatic symptoms and some somatoform disorders (e.g., hypochondriasis), and some personality disorders (mainly borderline and Cluster C personality disorders). The benefits of psychoanalytic and psychodynamic psychotherapies typically seem to endure well beyond the termination of treatment. In general, the outcomes achieved with these treatments appear to be equivalent to those gained through other psychotherapies. More definitive conclusions about the value of psychoanalysis and psychoanalytic psychotherapy cannot be drawn at this time. For a variety of reasons (e.g., the challenges associated with researching treatments that occur over long periods of time) there has been insufficient research conducted on the effectiveness of these psychotherapies, especially psychoanalysis. More research is required to strengthen the evidence base on the effectiveness of psychoanalysis and psychoanalytic psychotherapy.